POLA KOMUNIKASI BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI RIAU DALAM MENCEGAH DAN MENANGGULANGI BENCANA ASAP DI RIAU - Wahyudi, Firman; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Regional Disaster Management Agency (BPBD) Riau Province is a government agency established to disaster areas. As a government organization is certainly very necessary implementing communication patterns. Patterns of communication necessary for communication and Opera delivered the leadership can be accepted and understood subordinates. Delivering a message intended synergy of communication with the good cooperation so terapai goal of disaster management smog. This study aims to determine patterns of communication Regional Disaster Management Agency of Riau Province in disaster prevention and responses smoke in Riau.This study used a qualitative method with descriptive approach. This research is located in the Regional Disaster Management Agency of Riau Province, the General Sudirman, Pekanbaru with the object of study of communication patterns Regional Disaster Management Agency of Riau Province in disaster prevention and responses smoke in Riau. While the subject of research is chief executive BPBDs Riau Province, Head of Prevention and Preparedness, Emergency Head, Head of Rehabilitation and Reconstruction Task Force BPBDs Riau, Riau BPBDs Special Staff, Task Force for Disaster Resilient Village and BMKG Pekanbaru. Retrieving data using non-participant observation and interviews tersruktur and documentation.Results from this study indicate patterns of communication BPBDs Riau Province is a wheel pattern. Wheel pattern seen since the application of a structured communication and coordinated by BPBD Riau. At the time of the disaster prevents fumes, wheel pattern appears on the coordination done BPBDs Riau. At the time of tackling the disaster, the pattern wheel is used also in coordination and command and briefing at the command post BPBDs Riau. WhatApps strengthen the use of media usage patterns of the wheel. The whole stackholder can communicate with all the elements but still based on the existing structure.